Quantitative trait loci for Fusarium and Gibberella ear rot resistance in Argentinian maize germplasm - Giomi, Gerardo Mario; Iglesias, Juliana; Kreff, Enrique D.; Fauguel, Carolina Maria; Fernández, Mariana; Oviedo, María Silvina; Presello, Daniel Alberto (2017)
Fusarium verticillioides and F. graminearum cause ear rots in maize (Zea mays L.) that reduce yield and contaminate the grain with mycotoxins produced by the fungi. To map QTLs for resistance to these ear rots, a F5 mapping population, consisting of 298 recombinant inbreds obtained by randomly selfing of the cross between LP4637 (moderately resistant) and L4674 (susceptible), was genotyped with 250 single nucleotide polymorphism markers and phenotyped 2 years for disease severity after silk inoculation with conidial suspensions of F. verticillioides and F. graminearum. Four QTLs were mapped in chromosomes 2, 3 and 5, bins 2.03, 3.05, 3.07 and 5.07, explaining ranges of 11.2–11.8, 3.4–5.1, 6.2–7.6 and 3.8–5.0 of phenotypic variances (%), respectively, depending on year and fungus. Additive effects of each QTL ranged from 5.0 to 11.9 % of ear area covered by mold and no epistatic interactions were observed. The four QTLs were effective for both Fusarium species and environments indicating that LP4637 is a source of broad resistance to Fusarium stable across environments. These results are consistent with previous research reporting QTLs for ear rot resistance in the same chromosome regions from sources of resistance growing in North America, Africa, Europe and China.